ProteoSeeker: A Feature‐Rich Metagenomic Analysis Tool for Accessible and Comprehensive Metagenomic Exploration - Georgios Filis; Dimitra Bezantakou; Konstantinos Rigkos; Despina Noti; Pavlos Saridis; Dimitra Zarafeta; Georgios Skretas (Advanced Science, 2025)
Abstract The vast majority of microbial diversity remains unculturable, limiting access to novel biotechnological resources. Advances in metagenomics have expanded the understanding of microbial communities, yet targeted protein discovery remains challenging. This study introduces ProteoSeeker, a command‐line tool for streamlined metagenomic protein identification and annotation. ProteoSeeker operates in two primary modes: i) Seek mode, which screens the proteins according to user‐defined protein families, and ii) Taxonomy mode, which uncovers the taxonomy of the host organisms. By automating key steps, ProteoSeeker reduces computational complexity, enabling time‐efficient and comprehensive metagenomic analysis for both specialized and nonspecialized users. The efficiency of ProteoSeeker to achieve targeted enzyme discovery is demonstrated by identifying extremophilic enzymes with desired biochemical features, such as amylases for starch hydrolysis and carbonic anhydrases for CO₂ capture applications. By democratizing functional metagenomics, ProteoSeeker is anticipated to accelerate biotechnology, synthetic biology, and biomedical research and innovation.